Der rosenkavalier the rose-bearer, or the knight of the rose - Fisher, Burton D.; Opera Journeys Publishing (Opera Journeys mini guide series, 2000)
A comprehensive guide to Richard Strauss' DER ROSENKAVALIER, featuring Principal Characters in the opera, Brief Story Synopsis, Story Narrative with Music Highlight Examples, and an insightful and in depth Commentary and Analysis by Burton D. Fisher, noted opera author and lecturer.
Keywords: Strauss, Richard, : 1864-1949 : Rosenkavalier (Opera); Strauss, Richard, : 1864-1949 : Rosenkavalier (Opera) : Criticism and interpretation; Operas : Stories, plots, etc